Neutron scattering for surface characterization - Penfold, J (2000)
The use of the specular reflection of neutrons to provide information on the structure of surfaces and interfaces is described. Through hydrogen/deuterium isotopic substitution the refractive index distribution at interfaces can be manipulated, and this makes the technique particularly powerful for the study of the adsorption of polymers, surfactants, proteins and mixtures at interfaces. The technique has developed enormously in the last 10 years, and this will be illustrated with a range of recent examples from the scientific programme on the ISIS pulsed neutron source. Examples, which include the nature of polymer-polymer interfaces, and the adsorption of surfactants, proteins and polymers at different interfaces, will be used to illustrate the development towards the study of complex multi-component systems, 'buried' interfaces, and time-dependent phenomena, and in the use of complex environments.